BUSINESS MARKETING STRATEGY TO IMPROVE SALES OF PAKAYON NOODLES AT HOME INDUSTRY JAYA LESTARI, MANISA VILLAGE, BARANTI DISTRICT, SIDENRENG RAPPANG REGENCY - Muh Farham Setiady; Muh Thamrin; Bahtiar Herman (Universitas Nusa Cendana, 2026)
This study aims to analyze the marketing strategy implemented by Home Industry Jaya Lestari in increasing sales of its “Pakayon” noodle products and to formulate strategies that can sustain optimal sales beyond major events such as weddings or celebrations. The research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews with the business owner, production staff, and consumers, and analyzed using NVivo 15 Plus through coding and thematic analysis techniques. The findings indicate that product sales are heavily dependent on large-scale events, with the majority of transactions occurring during such occasions. This dependence is primarily attributed to limited digital promotion, insufficient product innovation tailored to daily consumption, restricted distribution channels, and the absence of a structured customer loyalty program. Nevertheless, the product’s key strengths lie in its distinctive taste, desirable noodle texture, and satisfactory customer service. The study recommends implementing product diversification, strengthening branding and digital marketing efforts, expanding distribution networks, conducting market education initiatives, and developing a customer loyalty program to encourage repeat purchases. By adopting more adaptive and innovative marketing strategies, Home Industry Jaya Lestari is expected to reduce reliance on seasonal demand and enhance business sustainability amid increasingly dynamic competition in the food industry. Keywords: Marketing Strategy; UMKM; Product Diversification; Digital Promotion; Customer Loyalty